The known large Near-Earth Objects’ highways: dynamical evolution, fates, and lifetimes - Liberato, Luana [UNESP]; Araújo, Rosana [UNESP]; Winter, Othon [UNESP] (Springer Nature, 2023)
It is well known that the Near-Earth Objects population is sustained by bodies that migrate inwards from the main asteroid belt and outer regions of the Solar System. In this work, we aim to revisit the dynamic evolution of the NEO population inside the Solar System using a known debiased population of large objects. Therefore, we separate the phase space into five different regions: Near-Earth Objects (NEO), Main Asteroid Belt (MAB), Jupiter Family Comets (JFC), Centaurs (CEN), and Trans-Neptunian Objects. We performed numerical simulations for 985 NEOs for 100 Myrs and tracked their transferences between regions to determine the most common routes and fates for this population. The results show that solar thermal disruption is the most efficient mechanism to remove NEOs because 70% of the studied objects are led to this fate. Also, 13% of the objects are ejected from the Solar System, representing a significant contribution of interstellar minor bodies from the NEO population. We find that, during their dynamical evolution, more than half of the objects are first transferred to the JFC region and an even larger percentage of them make their way out from the Solar System through it. There is also a significant frequent exchange of bodies between NEO and MAB regions. Almost 30% of the bodies move to the MAB region, but less than 1% of them end their lives inside it, so it seems that for this sample of objects, MAB is a transitional region where escaped NEOs briefly pass through. We also found that only about 14% of the bodies never leave the NEO region. From those, about half of them collide with the terrestrial planets, while the remaining either survive for the whole integration of 100 Myrs or move to a low pericenter orbit. Additionally, we show that almost 10% of the studied sample can reach the CEN region and remain there for a substantial amount of time, telling a different side of the story for the NEO population.